2009
DOI: 10.1117/1.3253320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laser parameters on nanoparticle-induced membrane permeabilization

Abstract: Light-absorbing nanoparticles that are heated by short laser pulses can transiently increase membrane permeability. We evaluate the membrane permeability by flow cytometry assaying of propidium iodide and fluorescein isothiocyanate dextran (FITC-D) using different laser sources. The dependence of the transfection efficiency on laser parameters such as pulse duration, irradiant exposure, and irradiation mode is investigated. For nano- and also picosecond irradiation, we show a parameter range where a reliable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…Recent efforts indicate that tuning the laser pulse parameters and properties of the absorbing particles can bias the mechanism towards a particular mode 95,96 . Although parameters are still being explored, a proof-of-concept study demonstrated conditions under which irradiation of gold nanoparticles was proposed to trigger localized thermal damage that permitted more than half of the treated cells to take up labelled antibodies 97 .…”
Section: Towards Precision Membrane Disruptionmentioning
confidence: 99%
“…Recent efforts indicate that tuning the laser pulse parameters and properties of the absorbing particles can bias the mechanism towards a particular mode 95,96 . Although parameters are still being explored, a proof-of-concept study demonstrated conditions under which irradiation of gold nanoparticles was proposed to trigger localized thermal damage that permitted more than half of the treated cells to take up labelled antibodies 97 .…”
Section: Towards Precision Membrane Disruptionmentioning
confidence: 99%
“…17,18 The use of a femtosecond laser with gold nanoparticles for the cell membrane perforation has also been reported. [19][20][21] In this method, collective free electron oscillation (surface plasmon) inside the gold particle generates a highly enhanced near field, resulting in the generation of cavitation bubbles and shock waves in the close vicinity of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody conjugated 30-nm nanospheres were used in their study. 3 Heinemann et al 1 presented a fully automated setup employing 850-ps pulses at 532 nm. The delivery of siRNA, Morpholinos, and dextrans of sizes up to 2000 kDa was demonstrated using this setup.…”
mentioning
confidence: 99%
“…© A versatile alternative to common transfection techniques, like electroporation and lipofection, is based on the interaction of laser irradiation and gold nanoparticles. [1][2][3] The routine procedure consists of the incubation of cells with gold nanoparticles with sizes of 80 to 200 nm for 3 to 6 h, which is sufficient for sedimentation for these large particles. 1,2,4 Alternatively, smaller antibody-conjugated particles are used.…”
mentioning
confidence: 99%
See 1 more Smart Citation